Adjusting to Globalization in Germany - Dauth, Wolfgang; Findeisen, Sebastian; Suedekum, Jens (Journal of Labor Economics, 2021)
We study the impact of trade exposure on the job biographies of 2.4 million manufacturing workers in Germany. Rising export opportunities lead to two equally important sources of earnings gains: on the job and employer switches within the same industry. Highly skilled workers benefit the most. Import shocks mostly hurt low-skilled workers, especially when they possess lots of industry-specific human capital. They also destroy workers’ rents when separating from high-wage plants, and they leave strongly scarring effects in the event of a mass layoff. We connect our results to the growing theoretical literature on the labor market effects of trade.